Práticas de leitura e produção de textos em diálogo com as práticas sociais dos sujeitos do campo: por uma interdiscursividade nas produções de textos orais e escritos - Pimenta, Ghane Kelly Gianizelli (2019)
This work shows a study developed around to pedagogical practice of text production in a multiseried classroom on the basis of reflection and understanding, the context of life of the countryside students. The general goal of the approach is to organize pedagogical practices of reading and text production which involves educator, learners and community in the challenge of a literacy as social practice that opening up the way of the necessary link of the school with living process and contradictory of the social life. The study deals with a participative research based on assumption of language bakhtinians and literacy as human social praxis. A inventory of data production was used to know the condictions and potentialities existing in the reality of the community of the learners. The analysis of the data employed the dialectic method which has as its principle the discursives, the historicity and social contradiction. The discursive practice of the text production developed from themes of the reality of the learners. The results showed that the production of text articulated with life themes enables reading acts and production of texts aimed at possibilities of actions that reverberate in the improvement of the life of people in community. From the results achieved in this research was produced a pedagogical book with proposals of actions/ interventions on multiseried classroom. As resulted it is expected to offer a contribution to production of knowledge in pedagogical practice based on establishment of the intrinsic relation between education and the context of life of the students